Simulation of laser-plasma interaction experiments with gas-filled hohlraums on the LIL facility. (March 2016) - Loiseau, P.; Masson-Laborde, P.-E.; Teychenné, D.; Monteil, M.-C.; Casanova, M.; Marion, D.; Tran, G.; Huser, G.; Rousseaux, C.; Hüller, S.; Héron, A.; Pesme, D.
Abstract: Laser-plasma interaction is a major issue for achieving ignition in inertial confinement fusion schemes, and still a major concern for the upcoming french laser mégajoule (LMJ) program. In order to mitigate the deleterious effects due to laser-plasma instabilities (LPI), clearly evidenced during the recent US National Ignition Campaign conducted on the National Ignition Facility, we use the LIL facility as a demonstrator for LPI studies. In this article, we focus on preliminary results regarding the propagation of a typical LMJ quadruplet through gas-filled hohlraums. Results on hohlraum energetics will then be discussed.